1970
DOI: 10.1111/j.1399-3054.1970.tb06466.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Induced Leaking of Organic Compounds from Boletus variegatus

Abstract: Addilion of oclanoic acid (2 • 10"^ M) to the suspending medium (final pH 4.85) of Bolettt.i uariegattts mycelium induced a marked leaking of UV absorhing substances from the celts. Ttie materiat hiid an absorption maximum at 260 nm, a minimum at 240 11111, and the absorption ratios 250: 260 and 280: 260 were 0.81 and 0.49.The material released immediately after addition of the acid consisted mainly of tow molecular weight substances. These suhslances, listed according to decreasing rates of leaking, were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It has been found that fatty acids with 10 or more C-atoms cause growth inhibition and a severe leakage of nucleotides from the mycelium of Fomes annosus (Johansson, unpublished results). This is a common effect of fatty acids (Lode and Pedersen 1970).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that fatty acids with 10 or more C-atoms cause growth inhibition and a severe leakage of nucleotides from the mycelium of Fomes annosus (Johansson, unpublished results). This is a common effect of fatty acids (Lode and Pedersen 1970).…”
Section: Discussionmentioning
confidence: 99%
“…as a test organism (PEDER-SEN, 1970;LODE and PEDERSEN, 1970). The authors concluded from in vitro experiments, that exogenously applied short-chain fatty acids, especially octanoic acid, rapidly interacted with lipophilic parts of the cell membranes leading to inhibition of respiration and leakage of low molecular weight compounds, such as pentoses, pentosphosphates, purine and pyrimidine bases, nucleosides, and mono-and dinucleotides.…”
Section: Choice Of Potential Marker Traitsmentioning
confidence: 99%
“…For instance, rishitin can cause membrane injuries (Lyon 1980) resembling those produced by some fatty acids (Lode and Pedersen 1970). However, very high concentrations of phytoalexins are usually required to cause such adverse reactions, and it is therefore uncertain as to whether they actually occur in nature.…”
Section: Toxicitymentioning
confidence: 99%
“…The cutting procedure sets lysosomes free in the tissues, and their enzymes may degrade constituents of the cell wall (Ray 1972) (Bostock et al 1981). Their effects, however, may be nonspecific, and they probably act by interfering with the lipoid parts of the host cell membrane, thereby impairing their function (Lode and Pedersen 1970). Since these two fatty acids are also found in the cell wall of the late blight fungus, it is also possible that treatment with sonicated mycelium elicits nonspecific reactions as well.…”
Section: Elicitationmentioning
confidence: 99%